2023
DOI: 10.3390/ijms24087436
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Immunostimulatory, and Anticancer Properties of Hydrolyzed Wheat Bran Mediated through Macrophages Stimulation

Abstract: Previous studies demonstrated that enzymatic hydrolysis enhances wheat bran (WB) biological properties. This study evaluated the immunostimulatory effect of a WB hydrolysate (HYD) and a mousse enriched with HYD (MH) before and after in vitro digestion on murine and human macrophages. The antiproliferative activity of the harvested macrophage supernatant on colorectal cancer (CRC) cells was also analyzed. MH showed significantly higher content than control mousse (M) in soluble poly- and oligosaccharides (OLSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Hydrolyzed WB was produced through the optimization of novel strategies to yield the highest concentration of soluble phenolic compounds, thereby maximizing the antioxidant and anti-inflammatory potential of the WB. Our previous studies have shown a reduction in TNF-α production in LPS-induced murine macrophages in the presence of this WB ingredient and an increased trend in most of the antioxidant parameters [8][9][10][11]. Other studies have also demonstrated, both in vitro and in vivo, the anti-inflammatory effects of FA.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hydrolyzed WB was produced through the optimization of novel strategies to yield the highest concentration of soluble phenolic compounds, thereby maximizing the antioxidant and anti-inflammatory potential of the WB. Our previous studies have shown a reduction in TNF-α production in LPS-induced murine macrophages in the presence of this WB ingredient and an increased trend in most of the antioxidant parameters [8][9][10][11]. Other studies have also demonstrated, both in vitro and in vivo, the anti-inflammatory effects of FA.…”
Section: Discussionmentioning
confidence: 72%
“…To improve the bioaccessibility, bioavailability, and ultimate bioactivity of this compound, our group has developed new technological strategies involving enzymatic hydrolysis combined with thermomechanical treatments. These approaches are designed to increase the ratio of free to bound FA content in WB, improving also their antioxidant and anti-inflammatory properties in vitro [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, enzymatic hydrolysis is another strategy, which, through the combination of cellulolytic and xylanolytic enzymes, can depolymerize the β-D-(1→4)-glucosidic and β-D-(1→4)-xylosidic bonds [ 33 ]. Different authors have determined that enzymatic hydrolysis allows the degradation of cell wall fibers, increasing the availability of phenolic compounds and β-glucan [ 20 , 25 , 34 ].…”
Section: Introductionmentioning
confidence: 99%